Delay tolerant networks protocols and applications - Vasilakos, Athanasios; Zhang, Yan, 1977-; Spyropoulos, Thrasyvoulos (Boca Raton : CRC Press, 2012)
"A class of Delay Tolerant Networks (DTN), which may violate one or more of the assumptions regarding the overall performance characteristics of the underlying links in order to achieve smooth operation, is rapidly growing in importance but may not be well served by the current end-to-end TCP/IP model. Delay Tolerant Networks: Protocols and Applications takes you on a systematic exploration of DTN concepts, architectures, protocols, enabling technologies, and applications.Containing a wealth of illustrative material for ease of understanding, this one-stop reference discusses the various challenges associated with DTN. Written for a broad audience of researchers and practitioners, it supplies useful reference material for graduate students and senior undergraduate students in courses of networking, wireless, and mobile communications. Starting with an accessible introduction to DTNs, their architecture, bundle protocols, and routing schemes, the book provides authoritative coverage of:DTN RoutingEnergy-Aware Routing Protocol for DTNsA Routing-Compatible Credit-Based Incentive SchemeR-P2P: a Data-Centric Middleware for Delay Tolerant ApplicationsMobile Peer-to-Peer Systems over DTNsDelay-Tolerant Monitoring of Mobility-Assisted WSNMessage Dissemination in Vehicular NetworksDTN Protocols for Space CommunicationsDTN for Satellite CommunicationsReporting on the latest developments in these domains, the distinguished panel of contributors supplies a realistic look into the future of networking. Complete with sections that summarize open issues in each domain, this book arms you with the understanding and methods required to make an impact on the advancement of these emerging networks that continue to grow in importance. "--
Includes bibliographical references.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Computer networks -- Reliability; Routing (Computer network management); Fault-tolerant computing; Electronic books